Effects of Gadodiamide and Gadoteric Acid on Rat Kidneys: A Comparative Study. Issue 2 (13th September 2018) - Celiker, Fatma Beyazal; Tumkaya, Levent; Mercantepe, Tolga; Beyazal, Mehmet; Turan, Arzu; Beyazal Polat, Hatice; Suzan, Zehra Topal; Inecikli, Mehmet Fatih; Akyildiz, Kerimali; Yilmaz, Adnan
Abstract : Background: Gadolinium‐based contrast agents are complex chelates to provide contrast in NRI. However, recent studies have highlighted the deposition of free Gd +3 ion in various tissues. Purpose: To evaluate the histopathological and immunohistochemical changes on rat kidney tissue following both macrocyclic (gadoteric acid) and linear (gadodiamide) agents under the hypothesis that gadolinium‐based contrast agents (GBCA) lead to toxic, free Gd +3 accumulation in tissues. Study Type: The local Animal Care Committee approved the prospective animal study. Animal Model: Thirty‐two healthy Sprague–Dawley male rats were administered 2 mmol/kg gadodiamide and gadoteric acid for the first 4 days for 5 weeks. Group 1 received no drug (control, n  = 8) and Group 2 ( n  = 8) was administered 0.1 ml/kg saline. Group 3 was administered 0.1 mmol/kg gadodiamide and Group 4 ( n  = 8) was administered 2 mmol/kg gadoteric acid. Assessment: Biochemical, histopathological, and immunohistochemical changes in testis kidney tissue were evaluated at the end of 10 weeks. Statistical Tests: Differences between groups were analyzed using the nonparametric Kruskal–Wallis test followed by one‐way analysis of variance and the Tamhane test, also followed by Turkey's HSD test. Results: Gadolinium increased serum urea, Ca +2, and Caspase‐3 positive tubular cell number. Larger Bowman capsules shrank proximal and distal tubules were revealed in the gadodiamide and gadoteric acid groups compared to the control group ( P  < 0.05). Histopathologic examination showed significantly more interstitial fibrosis, amyloid deposits, and vasocongestion in the gadodiamide group than the gadoteric acid and control groups, while the gadoteric acid group demonstrated significantly more leukocytic infiltration with atrophied proximal and distal tubules than the gadodiamide and control groups ( P  < 0.05). Data Conclusion: GBCA administration causes significant histopathologic changes in kidney tissue. This study advocates additional investigation to assess the in vivo safety of GBCAs. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;49:382–389.